2016
DOI: 10.1371/journal.pone.0148494
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Tau Class Glutathione-S-Transferases Gene (SbGSTU) Promoter of Salicornia brachiata under Salinity and Osmotic Stress

Abstract: Reactive oxygen or nitrogen species are generated in the plant cell during the extreme stress condition, which produces toxic compounds after reacting with the organic molecules. The glutathione-S-transferase (GST) enzymes play a significant role to detoxify these toxins and help in excretion or sequestration of them. In the present study, we have cloned 1023 bp long promoter region of tau class GST from an extreme halophyte Salicornia brachiata and functionally characterized using the transgenic approach in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 48 publications
(53 reference statements)
0
54
0
Order By: Relevance
“…The increased abundance of Prx proteins induced by AHL could be associated with the decreased MDA concentrations caused by lipid peroxidation in salt-stressed Arabidopsis seedlings. Furthermore, we identified a glutathione S-transferase tau 5 (spot 71) and a quinone oxidoreductase-like protein (spot 108), which had previously been reported to play a significant role to detoxify toxins generated in plant cell during the extreme stress condition (Heyno et al 2013, Tiwari et al 2016, showed increasing trend by all treatments. Interestingly, the maximum expression amounts of these two proteins were found in NaCl + AHL treatment, implying that exogenous AHL application can help to reduce the generation of toxic compounds in salt-stressed Arabidopsis seedlings.…”
Section: Defense/stress/detoxification-related Proteinsmentioning
confidence: 84%
“…The increased abundance of Prx proteins induced by AHL could be associated with the decreased MDA concentrations caused by lipid peroxidation in salt-stressed Arabidopsis seedlings. Furthermore, we identified a glutathione S-transferase tau 5 (spot 71) and a quinone oxidoreductase-like protein (spot 108), which had previously been reported to play a significant role to detoxify toxins generated in plant cell during the extreme stress condition (Heyno et al 2013, Tiwari et al 2016, showed increasing trend by all treatments. Interestingly, the maximum expression amounts of these two proteins were found in NaCl + AHL treatment, implying that exogenous AHL application can help to reduce the generation of toxic compounds in salt-stressed Arabidopsis seedlings.…”
Section: Defense/stress/detoxification-related Proteinsmentioning
confidence: 84%
“…thaliana (Sun, Gao, Zhao, Li, & Zhang, ). Several cis ‐regulatory elements and stress‐inducible motifs of different stress responsive genes have also been found in halophytes (Tiwari, Patel, Chaturvedi, Mishra, & Jha, ). The 897 bp promoter region of phosphoethanolamine N‐methyltransferase ( SlPEAMT ) gene isolated from S .…”
Section: Salt Tolerance Mechanisms In Halophytesmentioning
confidence: 99%
“…The AcBADH gene from Atriplex centralasiatica has been shown to be strongly induced by salt stress (Yin, Zhao, Luo, & Zhang, 2002 (Sun, Gao, Zhao, Li, & Zhang, 2010). Several cis-regulatory elements and stress-inducible motifs of different stress responsive genes have also been found in halophytes (Tiwari, Patel, Chaturvedi, Mishra, & Jha, 2016…”
Section: Molecular Signaturesmentioning
confidence: 99%
“…). Considering that the promoter expression activity of the walnut V‐ATPase G subunit ( JrVHAG1 ) was enhanced by CdCl 2 treatment (Xu et al ), that the expression of T. hispida c subunit ( ThVHAc1 ) promoter was increased by CdCl 2 and ThVHAc1 was further confirmed as Cd tolerance gene (Yang et al ), and that the GUS expression of Salicornia brachiata SbGSTU promoter was enhanced by PEG 6000 and salt stresses (Tiwari et al ), it can be concluded that JrGSTTau1 is a potential osmotic stress tolerance gene.…”
Section: Discussionmentioning
confidence: 99%